2005
DOI: 10.1097/01.brs.0000162282.46160.0a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Regions for Familial Idiopathic Scoliosis

Abstract: Linkage analyses have identified several candidate regions, a significant step in defining the genetic etiology of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
109
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 23 publications
4
109
1
2
Order By: Relevance
“…Wu et al have shown that Xbal site polymorphism of oestrogen receptor gene may be associated with a risk of AIS [60]. Despite continued efforts, as yet no single gene from these regions has been definitively linked to scoliosis [34].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Wu et al have shown that Xbal site polymorphism of oestrogen receptor gene may be associated with a risk of AIS [60]. Despite continued efforts, as yet no single gene from these regions has been definitively linked to scoliosis [34].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Relatives to patients with idiopathic scoliosis have a higher prevalence of this condition than the population in general, suggesting the importance of hereditary factors [1][2][3]. Pedigree studies and genetic analyses have so far shown inconsistent results both regarding the mode of heritability and possible genetic determinants associated with the scoliotic phenotype [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…5 Inoue et al 6 reported AIS concordance rates as 92.3% in monozygotic twins, and 62.5% in dizygotic twins. Recent genome-wide linkage analyses have identified many predisposing loci of AIS, [7][8][9][10][11][12][13][14][15][16] further supporting a role of genetic factor(s) in AIS. Single nucleotide polymorphisms (SNPs) in the genes for estrogen receptor 1 (ESR1), 17 estrogen receptor 2 (ESR2), 18 matrilin 1 (MATN1), 19 melatonin receptor 1B (MTNR1B), 20 and tryptophan hydroxylase 1 (TPH1) 21 are reported to be associated with AIS predisposition.…”
mentioning
confidence: 99%